ROLE OF ANTIOXIDANTS CYSTEINE AND TAURINE IN TRIS EGG YOLK BASED EXTENDER FOR CRYOPRESERVATION OF SURTI BUFFALO SEMEN - VARGHESE, ORIN; DHAMI, A J; HADIYA, K K; PATEL, J A; PARMAR, S C (The Indian Journal of Animal Reproduction, 2023)
The study was undertaken on 40 semen ejaculates collected from 5 Surti bulls (8 ejaculates per bull).Ejaculates with >70% initial motility were split into 5 equal fractions and were diluted with standard Tris citrate fructose egg yolk glycerol (TFYG) extender as control and TFYG having 2 additives Cysteine HCI (0.5 & 1.0 mg/ml) and Taurine (4.0 & 6.0 mg/ml) each at 2 levels to study their comparative efficacy for cryopreservation of buffalo spermatozoa. After 12-24 hrs of cryopreservation, each of the 5 split-samples were thawed in water bath at 37°C for 30 seconds and observed for post-thaw motility, viability, morphology, acrosomal integrity and plasma membrane integrity. The post-thaw longevity of sperm at 37°C incubation was also studied for 3 hrs. Highly significant (P
Keywords: Buffalo semen; Cryopreservation; Semen extender; Antioxidants; Cysteine HCI; Taurine; Sperm quality